Effect of age and biological sex on performance in sprint, olympic half-ironman and ironman distance triathlons. - Wu, S. S. X.; Pfeiffer, J. J.; Nosaka, K.; Abbiss, C. R. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
A number of studies have examined the influence of biological sex and age on exercise performance [1]. However, little is known with regards to the interaction of differing modes of locomotion and exercise duration with these factors. The purpose of this study was to examine the interaction of biological sex and age on performance over the three disciplines of triathlon during events of varying distance. Methods: Time for each discipline (swimming, cycling, and running) and overall finishing times of the top 20% of male and female amateur triathletes performing in various age groups (i.e. decade of age >20y) of four standard distance triathlons were examined. The triathlon distances included a sprint (0.75 km swim, 20 km cycle, 5 km run, n=68) an Olympic (1.5 km swim, 40 km cycle, 10 km run, n=76), a half-Ironman (1.9 km swim, 90 km cycle, 21.1 km run, n=256), and an Ironman (3.8 km swim, 180 km cycle, 42.2 km run, n=234). Overall race data was obtained from official event websites. For each event and discipline, performance time of each triathlete was normalised to the fastest age group of the respective sex. Results: An age related decline in overall performance during the half-Ironman was observed beyond 40 y for males (P=0.021) and females (P=0.001). Performance decline in the Ironman was observed from 40 y for males and 50 y in females (P=0.018). The age related decline in overall performance was not significantly different between males and females during the sprint and Olympic distance triathlons. Swimming performance of both males (P=0.011) and females (P=0.002) was significantly better in younger (20-29 y) compared with athletes 30 y and older in all events. Fastest cycling times for males was observed at age 30-39 y irrespective of race distance, while females were fastest at age 40-49 y in all events, except for the half-Ironman where 20-29 y were fastest (P=0.034). An age related decline in running performance was observed in the half-Ironman and Ironman > 40 y in males (P=0.009), > 40 y (P=0.001) and 50 y (P=0.012) in females, respectively. Discussion: Results from the present study indicate that the age related decline in overall performance in both males and female athletes was more evident in the longer distances (Ironman and half-Ironman), compared with shorter events [2]. These differences appear to be closely associated with decreases in running performance. Further research is needed to understand the physiological factors responsible for age related declines in exercise performance of differing duration and locomotion.